Kids on the Move: The Effects of a Short-Term Physical Activity Program in a Group of Rural Elementary School Students - Kim Curry; Elmire D. Cantey; Carol Rykard (University of North Florida, 2005)
Obesity and physical inactivity are serious problems in the United States. Through a grant awarded by the Florida Department of Health, school health providers at the Madison County Health Department undertook a study to assess measurable impact of a basic physical activity program in a convenience sample of elementary school students. Using pedometers and other student incentives, the school health staff worked with teachers and administrators to implement an exercise program for 379 students. At the conclusion of the study, 364 students had completed both baseline and follow up measurements for age, gender, height, weight, body mass index calculation, and blood pressure. A surprisingly high proportion of students were found to have a high body mass index upon initiation of the study. Body mass index declined slightly in each group over the course of the study. However, there was not a corresponding decrease in blood pressure within each group. The results demonstrated some measurable benefit of a physical activity program in this group of students.